Limits of the Concept of Fair Use in Law number 28 of 2014 concerning Copyright - Sardjana Orba Manullang; Mutiarany; Louisa Yesami Krisnalita; Yessy Kusumadewi; Verawati Br Tompul (Jurnal Hukum dan HAM Wara Sains, 2023)
As social beings, people frequently run into intellectual property issues in their relationships. God created humans as complex beings with a variety of needs in order to function. The ingredients required by humans to sustain physiological and psychological equilibrium, which attempts to maintain life and health, are also basic human requirements. There are a number of things that might lead to copyright infringement in Indonesia, from lax government regulations to a lack of public understanding of the value of copyright and the protection of intellectual property rights. However, because of the fair use doctrine, copyright is not entirely controlled by the inventor or copyright holders. The Fair Use Limit Concept in Law Number 28 of 2014 Concerning Copyright is the formulation of the problem in this study, which seeks to determine how far the Fair Use Limit Concept is in Law Number 28 of 2014 Concerning Copyright, the methodology utilized in This study employs a type of normative research that involves reading reviews of secondary sources of information. This study also takes into account and examines copyright laws and regulations. The study's findings demonstrate that Indonesia's fair use laws are appropriately evaluated by the presence of the author's name or the use's noncommercial intent. In Indonesia, fair use laws give more people the chance to work and develop their creativity by utilizing the works of others. This is consistent with the essence of copyright, which requires that individuals produce specific works, which in this instance can be accomplished through the modification of other individuals' copyrighted works.